2020
DOI: 10.1001/jamaoncol.2019.5570
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Immune-Related Adverse Events and Recurrence-Free Survival Among Patients With Stage III Melanoma Randomized to Receive Pembrolizumab or Placebo

Abstract: IMPORTANCE Whether immune-related adverse events (irAEs) indicate drug activity in patients treated with immune checkpoint inhibitors remains unknown.OBJECTIVE To investigate the association between irAEs and recurrence-free survival (RFS) in the double-blind EORTC 1325/KEYNOTE-054 clinical trial comparing pembrolizumab therapy and placebo for the treatment of patients with high-risk stage III melanoma. DESIGN, SETTING, AND PARTICIPANTSA total of 1019 adults with stage III melanoma were randomly assigned on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
256
5
24

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 339 publications
(304 citation statements)
references
References 32 publications
19
256
5
24
Order By: Relevance
“…In this trial, the 15-month incidence of immune-related adverse events was 37% with pembrolizumab versus 9% with placebo [15]. The incidence of adverse events with pembrolizumab was 29% at 6months, so reducing treatment duration to 6 months would not have a major impact on reducing adverse event rate or improving the risk: benefit ratio of treatment.…”
Section: Key Pointsmentioning
confidence: 78%
See 1 more Smart Citation
“…In this trial, the 15-month incidence of immune-related adverse events was 37% with pembrolizumab versus 9% with placebo [15]. The incidence of adverse events with pembrolizumab was 29% at 6months, so reducing treatment duration to 6 months would not have a major impact on reducing adverse event rate or improving the risk: benefit ratio of treatment.…”
Section: Key Pointsmentioning
confidence: 78%
“…However, the occurrence of an immune-related adverse event was significantly associated with a longer RFS in the pembrolizumab arm (HR 0.61), but not the placebo arm. Thus immune-related adverse events may be an indicator of a beneficial host immune response [15].…”
Section: Key Pointsmentioning
confidence: 99%
“…The occurrence of an irAEs was associated with a longer recurrence free survival in the pembrolizumab arm. 102 Rheumatic disorders are interesting predictors of response. Kostine et al showed a better tumour response rate for patients with rheumatic AEs compared with patients without rheumatic AEs (85.7% vs 35.3%; P<0.0001).…”
Section: Toxicity -Efficacy Relationshipmentioning
confidence: 99%
“…Hier wurden Amylase-Erhöhungen ≥ Grad 3 in 0,3 % der Patienten unter PD-1/PD-L1-Inhibition beobachtet [7]. [4,41,42]. Unter Kombinationstherapie kommen häufiger mehrere endokrine Nebenwirkungen vor [2,43].…”
Section: Inflammatorische Hepatotoxizität Und Pankreasunclassified